Broadband-gap perovskite solar cell with high open-circuit voltage and preparation method thereof
By introducing derivative molecules of ethylenediamine and phenethylamine and their halide salt materials as buried interface modification layers in wide-bandgap perovskite solar cells, the challenges of perovskite solar cells in terms of photoelectric conversion efficiency and stability are solved, and higher open circuit voltage and photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202411770285.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Wide-bandgap perovskite solar cells have many challenges in photoelectric conversion efficiency and stability, including light-induced phase separation, ion migration, thermal and humidity stability, and interface recombination problems.
By introducing derivative molecules of ethylenediamine and phenethylamine and their corresponding halide salt materials as buried interface modification layers below the perovskite absorbing layer of wide-bandgap perovskite solar cells, the crystallization process of perovskite films is optimized and the interfacial energy level mismatch problem is alleviated.
The open circuit voltage of wide-bandgap perovskite solar cells is significantly improved to above 1.41V, the crystallization quality and carrier transmission efficiency of the film are improved, and the photoelectric conversion efficiency and long-term stability of the battery are improved.
Smart Images

Figure CN119677290A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a wide bandgap perovskite solar cell with high open circuit voltage and a preparation method thereof. Background Art
[0002] In the field of photovoltaics, traditional single-junction solar cells are close to their theoretical efficiency limit, and by stacking cell materials with different band gaps, tandem solar cells (Tandem Solar Cells) can break through this limitation. Silicon, as a mature substrate cell material, has established a complete theoretical system and process technology. Perovskite materials are considered to be ideal candidate materials for manufacturing top cells of tandem solar cells due to their excellent light absorption coefficient, adjustable band gap and low-cost solution processing characteristics. Theoretically, the photoelectric conversion efficiency (PCE) of perovskite / perovskite / crystalline silicon triple-junction tandem solar cells can reach about 51%, greatly exceeding the efficiency limit of single-junction cells. Therefore, among the many tandem solar cell technologies, perovskite / perovskite / crystalline silicon triple-junction tandem solar cells have become a research hotspot due to their potential high efficiency.
[0003] To date, the PCE of perovskite / perovskite / crystalline silicon triple-junction tandem solar cells has exceeded 27%, showing certain development prospects. However, there is still a significant gap between the currently achieved performance and its theoretical limit PCE, and there are still many problems that need to be solved. Among them, wide-bandgap perovskite solar cells, as a key component of perovskite / perovskite / crystalline silicon triple-junction tandem solar cells, have made significant progress in material design and optoelectronic performance optimization, but still face many challenges, such as photoinduced phase separation, ion migration, thermal and humidity stability, and interface recombination. How to improve the photoelectric conversion efficiency of wide-bandgap perovskite solar cells while ensuring stability is one of the urgent problems to be solved in current research.
[0004] In addition to optimizing the perovskite composition and crystallization kinetics, interface engineering has been used as an effective method to improve the efficiency and stability of perovskite solar cells. However, traditional interface treatment methods mainly focus on the upper interface between the perovskite and the electron transport layer in the trans structure. There are also a series of problems between the hole transport layer and the wide-bandgap perovskite light-absorbing layer, including poor crystallization quality of wide-bandgap perovskite films due to poor hydrophilicity of the hole transport layer material, and carrier interface accumulation caused by energy level mismatch between the hole transport layer material and the wide-bandgap perovskite material. These problems have also seriously restricted the development of wide-bandgap perovskite solar cells. Summary of the invention
[0005] In view of this, the present invention provides a wide bandgap perovskite solar cell with high open circuit voltage and a preparation method thereof. Aiming at the above-mentioned problems encountered by the top wide bandgap perovskite in the wide bandgap perovskite / intermediate bandgap perovskite / narrow bandgap crystalline silicon triple-junction tandem solar cell, a buried interface modification method using derivative molecules of ethylenediamine and phenylethylamine and their corresponding halide salt materials is used to optimize the crystallization process of the wide bandgap perovskite film, and at the same time alleviate the interface energy level mismatch problem, thereby significantly increasing the open circuit voltage of the wide bandgap battery to above 1.41V, which has the potential to promote the rapid development of high-efficiency triple-junction tandem battery technology.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A wide bandgap perovskite solar cell with high open circuit voltage comprises an ITO conductive glass, a hole transport layer, a buried interface modification layer, a wide bandgap perovskite light absorbing layer, a wide bandgap perovskite light absorbing layer, an electron transport layer, a buffer layer and a metal electrode layer which are sequentially deposited on the ITO conductive glass; the buried interface modification layer is a film prepared by mixing one or at least two of derivative molecules of ethylenediamine, phenylethylamine and their corresponding halide salts (for example: ethylenediamine dihydroiodate, phenylethylammonium bromide) in any proportion.
[0008] Furthermore, the hole transport layer is a composite structure made of nickel oxide (NiOx) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz).
[0009] Furthermore, the material used for the electron transport layer is [6,6]-phenyl-C61-butyric acid isomethyl ester (PCBM); and the material used for the buffer layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).
[0010] A method for preparing a wide bandgap perovskite solar cell with high open circuit voltage comprises the following steps:
[0011] Step 1, cleaning and drying the ITO conductive glass; placing it in a UV-ozone cleaning device, and treating it with UV-ozone for 15min to 30min in an atmospheric atmosphere and room temperature;
[0012] Step 2, preparing a hole transport layer on the ITO conductive glass obtained in step 1 by spin coating;
[0013] Step 3, dissolving phenethylammonium bromide (PEABr) in DMSO to obtain a PEABr solution with a concentration of 0.5-1 mg / mL; then spin-coating the PEABr solution on the hole transport layer through a spin coater at a spin coating speed of 3000-4000 rpm for 5-10 seconds to obtain a buried interface modification layer;
[0014] Step 4, preparing a wide bandgap perovskite precursor solution, spin-coating the wide bandgap perovskite precursor solution on the buried interface modification layer by an anti-solvent method, and preparing a wide bandgap perovskite light-absorbing layer by annealing;
[0015] Step 5: depositing an electron transport layer, a buffer layer and a metal electrode in sequence on the wide bandgap perovskite light-absorbing layer to obtain a wide bandgap perovskite solar cell with a high open circuit voltage.
[0016] Furthermore, the implementation method of step 2 includes the following steps:
[0017] Step 2.1: Dissolve NiOx nanoparticles in deionized water to prepare a NiOx nanodispersed solution with a concentration of 10 to 20 mg / mL;
[0018] Step 2.2: Spin the NiOx solution onto the ITO conductive glass using a spin coater at a spin coating speed of 3000-4000 rpm for 30-40 s, and then anneal on a hot stage at 100-120° C. for 10-15 min;
[0019] Step 2.3: Dissolve Me-4PACz in anhydrous ethanol to prepare a Me-4PACz solution with a concentration of 0.5-1 mg / mL.
[0020] Step 2.4: Spin coat the Me-4PACz solution on the product obtained in step 2.2 at a speed of 3000-4000 rpm for 30-40 seconds, and then anneal on a hot stage at 100-120°C for 10-15 minutes to obtain a hole transport layer.
[0021] Furthermore, the implementation method of step 4 includes the following steps:
[0022] Step 4.1: Press Recipe Cs 0.1 MA 0.1 FA 0.8 PbI 1.8 Cl 0.2 preparing a wide bandgap perovskite precursor solution;
[0023] Step 4.2: Spin the prepared wide bandgap perovskite precursor solution onto the obtained buried interface modification layer by a spin coater. The rotation speed of the spin coater is divided into two stages. The rotation speed of the first stage is 1000-2000 rpm and the spinning time is 10 s. The rotation speed of the second stage is 4000-5000 rpm and the spinning time is 40 s. At the beginning of the second stage, 0.1-0.2 mL of chlorobenzene anti-solvent is added dropwise onto the rotating substrate surface for 20-25 s. After the second stage of spin coating is completed, annealing is performed at a temperature range of 80-100°C for 10-15 min to obtain a wide bandgap perovskite light-absorbing layer.
[0024] Furthermore, the implementation method of step 5 includes the following steps:
[0025] Preparation of electron transport layer: PCBM is dissolved in chlorobenzene (CB) to prepare a PCBM solution with a concentration of 15 mg / mL; the solution is spin-coated on the wide bandgap perovskite light-absorbing layer by a spin coater at a spin coating speed of 1000 to 2000 rpm for 30 to 40 seconds, and then annealed on a hot stage at a temperature range of 100 to 120° C. for 5 to 10 minutes to obtain the electron transport layer;
[0026] Preparation of buffer layer: BCP was dissolved in isopropyl alcohol (IPA) to prepare a BCP solution with a concentration of 2 mg / mL; the solution was spin-coated on the electron transport layer by a spin coater at a speed of 4000 to 5000 rpm for 20 to 30 seconds, and then annealed on a hot stage at a temperature range of 80 to 100°C for 1 to 3 minutes to obtain a buffer layer.
[0027] The present invention significantly improves the performance of the battery by introducing derivative molecules of ethylenediamine and phenylethylamine and their corresponding halide salt materials as a buried interface modification layer under the perovskite light absorption layer of the wide-bandgap perovskite solar cell. The derivative molecules of ethylenediamine and phenylethylamine and their corresponding halide salt materials can provide free electron pairs, which can react with uncoordinated Pb in the wide-bandgap perovskite during the preparation of the wide-bandgap perovskite film. 2+ A stable coordination structure is formed to achieve the regulation of the perovskite crystallization dynamics and improve the crystallization quality of the wide-bandgap perovskite film. At the same time, the energy level matching degree between the modified hole transport layer and the perovskite light-absorbing layer is higher. This optimization effectively reduces the energy level barrier of the carriers at the interface between the perovskite layer and the hole transport layer, promotes the rapid extraction of carriers, and reduces energy loss. In addition, the hydrophilicity of the modified hole transport layer is also improved, which solves the problem of poor film-forming properties of the wide-bandgap perovskite solar cell on the surface of the self-assembled molecular layer with poor hydrophilicity, and further optimizes the carrier transmission efficiency. These improvements not only improve the film quality of the wide-bandgap perovskite light-absorbing layer, but also reduce the voltage loss of the inverted perovskite solar cell under open circuit conditions, ultimately enabling the cell to achieve higher photoelectric conversion efficiency and better long-term stability. Through this innovative buried interface modification strategy, the present invention provides an effective solution for the performance optimization of wide-bandgap perovskite solar cells.
[0028] In summary, the present invention can at least achieve the following beneficial effects:
[0029] 1. The method for preparing a wide bandgap perovskite film proposed in the present invention, by finely regulating the buried interface between the perovskite and the hole transport layer, not only improves the crystallization quality of the perovskite, but also significantly reduces the interface energy level barrier for carrier transport, accelerates carrier extraction, and reduces energy loss, thereby laying a solid material foundation for the manufacture of high-performance perovskite solar cells.
[0030] 2. The present invention proposes a method for preparing a wide bandgap perovskite film, which can significantly reduce the open circuit voltage loss of an inverse perovskite solar cell during operation. This technical improvement effectively enhances the photoelectric conversion efficiency of solar cells, thereby providing an innovative technical approach to improving the efficiency of solar energy utilization. Through the application of this preparation method, the present invention opens up a new research direction for the advancement of solar cell technology and efficiency improvement.
[0031] 3. The method for preparing a wide bandgap perovskite film proposed in the present invention has excellent compatibility with the production process of perovskite-perovskite-silicon triple-junction tandem solar cells and can be integrated into the preparation process of a wide bandgap perovskite light-absorbing layer. This integration strategy not only promotes the further optimization of the performance of perovskite-perovskite-silicon triple-junction tandem solar cells, but also provides a new direction for the development of solar cell technology with higher photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the solar cell structure of the comparative example.
[0033] Figure 2 Schematic diagram of the solar cell structure of the embodiment.
[0034] Figure 3 The morphology of the wide bandgap perovskite film surface under a scanning electron microscope (SEM) of the comparative example and the embodiment.
[0035] Figure 4 1 is the X-ray diffraction (XRD) spectrum of the wide bandgap perovskite film of the comparative example and the embodiment.
[0036] Figure 5 The figure is a current density-voltage (JV) curve of the inverse perovskite solar cell obtained in the comparative example and the embodiment. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with the examples and the accompanying drawings. Where specific experimental steps or conditions are not specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. Where the manufacturers of the reagents or instruments used are not specified, they are all conventional reagent products that can be purchased.
[0038] Example 1
[0039] This embodiment provides a method for preparing an inverse perovskite solar cell, which includes the method for preparing the wide bandgap perovskite film 1 proposed in the present invention, comprising the following steps:
[0040] Step 1: Clean the substrate:
[0041] In this embodiment, indium tin oxide (ITO) glass is selected as the substrate; first, deionized water, acetone, and anhydrous ethanol are used for ultrasonic cleaning for 15 minutes each, the washed substrate is blown dry with a nitrogen gun and stored in a dry environment, and treated with a UV-ozone cleaning device for 30 minutes before use.
[0042] Step 2: Preparation of hole transport layer:
[0043] In this embodiment, a composite structure of nickel oxide (NiOx) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) is used as the hole transport layer, and the preparation steps are as follows:
[0044] Step 2.1: Weigh a certain amount of NiOx nanoparticles and dissolve them in deionized water to prepare a NiOx nanodispersed solution with a concentration of 10 mg / mL.
[0045] Step 2.2: Spin the NiOx solution onto the ITO substrate using a spin coater at a speed of 4000 rpm for 30 s, and then anneal on a hot stage at 100°C for 10 min.
[0046] Step 2.3: Weigh a certain amount of Me-4PACz and dissolve it in anhydrous ethanol to prepare a Me-4PACz solution with a concentration of 1 mg / mL.
[0047] Step 2.4: Spin the Me-4PACz solution onto the NiOx surface using a spin coater at a spin coating speed of 3000 rpm for 30 seconds, and then anneal on a hot stage at 100° C. for 10 minutes to obtain a hole transport layer.
[0048] Step 3: Prepare the buried interface modification layer
[0049] Step 3.1: dissolving phenethylammonium bromide (PEABr) in DMSO to obtain a PEABr solution with a concentration of 0.5 to 1 mg / mL;
[0050] Step 3.2: Spin coat the PEABr solution on the hole transport layer using a spin coater at a spin coating speed of 4000 rpm for 10 s to obtain a buried interface modification layer;
[0051] Step 4: Preparation of wide bandgap perovskite layer:
[0052] Step 4.1: Prepare wide bandgap perovskite precursor solution: weigh 26.0 mg of CsI, 15.9 mg of MAI, 137.6 mg of FAI, 330.3 mg of PbBr 2 , 27.8 mg of PbCl 2 The mixture was dissolved in 1 mL of a mixed solvent and stirred for 12 h. The mixed solvent consisted of dimethylformamide (DMF) and DMSO, and the volume ratio of DMF to DMSO was 4:1, thereby obtaining a wide bandgap perovskite precursor solution.
[0053] Step 4.2: Spin coating perovskite film: The wide bandgap perovskite precursor solution is spin coated on the obtained buried interface modification layer by a spin coater. The rotation speed of the spin coater is divided into two stages. The rotation speed of the first stage is 1000 rpm and the duration is 10 s. The rotation speed of the second stage is 4000 rpm and the duration is 40 s. At 25 s in the second stage, 0.15 mL of chlorobenzene antisolvent is dropped on the surface of the rotating perovskite precursor solution.
[0054] Step 4.3: Film annealing: Place the spin-coated sample on a hot stage and anneal at 100° C. for 10 min to obtain a wide bandgap perovskite film.
[0055] Step 5: Preparation of electron transport layer:
[0056] In this embodiment, [6,6]-phenyl-C61-butyric acid isomethyl ester (PCBM) is selected as the electron transport layer material, and the preparation steps are as follows:
[0057] Step 5.1: Weigh a certain amount of PCBM and dissolve it in chlorobenzene (CB) to prepare a PCBM solution with a concentration of 15 mg / mL.
[0058] Step 5.2: Spin the PCBM solution onto the surface of the wide bandgap perovskite film using a spin coater at a spin coating speed of 1500 rpm for 30 seconds, followed by annealing at 100°C on a hot stage for 5 minutes.
[0059] Step 6: Prepare the buffer layer:
[0060] In this embodiment, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) is selected as the buffer layer material, and the preparation steps are as follows:
[0061] Step 6.1: Weigh a certain amount of BCP and dissolve it in isopropyl alcohol (IPA) to prepare a BCP solution with a concentration of 2 mg / mL.
[0062] Step 6.2: Spin the BCP solution onto the PCBM surface using a spin coater at a spin coating speed of 5000 rpm for 20 seconds, and then anneal on a hot stage at 80° C. for 1 minute. Thus, an electron transport layer is obtained.
[0063] Step 7: Preparation of metal electrodes:
[0064] In this embodiment, silver is selected as the metal electrode, and the preparation method is: 120nm of silver is deposited on the surface of the electron transport layer by vacuum thermal evaporation through a mask. Figure 2 The completed wide-bandgap perovskite solar cell shown.
[0065] Example 2
[0066] This comparative example provides a method for preparing an inverse perovskite solar cell. The preparation steps are basically the same as those in Example 1, except that the material used in the buried interface modification layer in Example 2 is ethylenediamine dihydroiodate.
[0067] Comparative Example
[0068] This comparative example provides a method for preparing an inverse perovskite solar cell. The preparation steps are basically the same as those in Example 1, except that: in the comparative example, after depositing the hole transport layer, there is no need to deposit a buried interface modification layer, and the obtained wide bandgap perovskite precursor solution is directly spin-coated on the hole transport layer by a spin coater. The structure is as follows: Figure 1 shown.
[0069] The above comparative examples and embodiments are analyzed and tested below:
[0070] The wide bandgap perovskite films obtained in the examples and comparative examples were subjected to SEM analysis, and the results are as follows: Figure 3 As shown, Figure 3 (a) corresponding to the film obtained in the corresponding ratio, Figure 3 (b) corresponds to the film obtained in Example 1, Figure 3 (c) The film obtained in Example 2. Compared with the comparative example, the wide bandgap perovskite film after the buried interface modification treatment not only has a significantly larger grain size, but also has clearer grain boundaries. This makes the wide bandgap perovskite film have a better surface morphology, indicating that it has good crystal quality.
[0071] XRD analysis was performed on the wide bandgap perovskite films obtained in the examples and comparative examples. The results are as follows: Figure 4As shown in the figure, compared with the comparative example, after the buried interface modification treatment is performed in Example 1 and Example 2, the intensity of the characteristic peak of the perovskite (corresponding to a 2θ value of 14.6°) increases to a certain extent, reflecting the good crystallinity of the perovskite; at the same time, after the buried interface modification treatment is performed in the example, the characteristic peak of the secondary phase (corresponding to a 2θ value of 11.8°) is greatly reduced, indicating that PEABr, EDADI and the uncoordinated Pb in the perovskite 2+ The ions form a stable coordination structure, which reduces the generation of non-photoactive phases and improves the crystallization quality of wide-bandgap perovskite films.
[0072] Photovoltaic tests were performed on the inverse perovskite solar cells obtained in the examples and comparative examples, and the effective active area was 0.053 cm 2 The test conditions are standard simulated sunlight AM1.5 G and a temperature of 25°C. The JV curves of the embodiment and the comparative example are shown in FIG. Figure 5 As shown, the open circuit voltage of the inverse perovskite solar cell obtained in Example 1 is 1.40V and the short circuit current is 13.3mA / cm 2 , the fill factor is 73.7%, and the energy conversion efficiency is 13.8%; the open circuit voltage of the inverse perovskite solar cell obtained in Example 2 is 1.41V, and the short circuit current is 13.0mA / cm 2 , the fill factor is 73.3%, and the energy conversion efficiency is 13.5%; the open circuit voltage of the inverse perovskite solar cell obtained in the comparative example is 1.37V, and the short circuit current is 12.5mA / cm 2 , the filling factor is 73.0%, and the energy conversion efficiency is 12.4%. Compared with the comparative example, the open circuit voltage of the embodiment is significantly improved, and the improvement in the filling factor also indicates that the carrier transmission capacity is improved, which shows that the photovoltaic performance of the solar cell device is optimized under the effect of the buried interface modification of the wide bandgap perovskite film.
[0073] The photovoltaic parameters of the inverse perovskite solar cells obtained in the embodiments of the present invention and the comparative examples are shown in Table 1:
[0074] Table 1:
[0075]
[0076] The above embodiments are intended to provide a better understanding of the present invention, but are not limited to the optimal implementation mode and do not constitute a limitation on the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts shall be within the protection scope of the present invention.
Claims
1. A wide bandgap perovskite solar cell with high open circuit voltage, characterized in that: The invention comprises an ITO conductive glass, a hole transport layer, a buried interface modification layer, a wide bandgap perovskite light absorption layer, a wide bandgap perovskite light absorption layer, an electron transport layer, a buffer layer and a metal electrode layer which are sequentially deposited on the ITO conductive glass; the buried interface modification layer is a film prepared by mixing one or at least two of the derivative molecules of ethylenediamine, phenylethylamine and their corresponding halide salts in any proportion.
2. A wide bandgap perovskite solar cell with high open circuit voltage according to claim 1, characterized in that: The hole transport layer is a composite structure made of nickel oxide (NiOx) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz).
3. A wide bandgap perovskite solar cell with high open circuit voltage according to claim 1, characterized in that: The material used in the electron transport layer is [6,6]-phenyl-C61-butyric acid isomethyl ester (PCBM); the material used in the buffer layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).
4. A method for preparing a wide bandgap perovskite solar cell with high open circuit voltage, characterized in that: The following steps are involved: Step 1, cleaning and drying the ITO conductive glass; placing it in a UV-ozone cleaning device, and treating it with UV-ozone for 15min to 30min in an atmospheric atmosphere and room temperature; Step 2, preparing a hole transport layer on the ITO conductive glass obtained in step 1 by spin coating; Step 3, dissolving phenethylammonium bromide (PEABr) in DMSO to obtain a PEABr solution with a concentration of 0.5-1 mg / mL; then spin-coating the PEABr solution on the hole transport layer with a spin coating apparatus at a speed of 3000-4000 rpm for 5-10 seconds to obtain a buried interface modification layer; Step 4, preparing a wide bandgap perovskite precursor solution, spin-coating the wide bandgap perovskite precursor solution on the buried interface modification layer by an anti-solvent method, and preparing a wide bandgap perovskite light-absorbing layer by annealing; Step 5: depositing an electron transport layer, a buffer layer and a metal electrode in sequence on the wide bandgap perovskite light-absorbing layer to obtain a wide bandgap perovskite solar cell with a high open circuit voltage.
5. The method for preparing a wide bandgap perovskite solar cell with high open circuit voltage according to claim 4, characterized in that: The implementation method of step 2 comprises the following steps: Step 2.1: Dissolve NiOx nanoparticles in deionized water to prepare a NiOx nanodispersed solution with a concentration of 10 to 20 mg / mL; Step 2.2: Spin the NiOx solution onto the ITO conductive glass using a spin coater at a spin coating speed of 3000-4000 rpm for 30-40 s, and then anneal on a hot stage at 100-120° C. for 10-15 min; Step 2.3: Dissolve Me-4PACz in anhydrous ethanol to prepare a Me-4PACz solution with a concentration of 0.5-1 mg / mL. Step 2.4: Spin coat the Me-4PACz solution on the product obtained in step 2.2 at a speed of 3000-4000 rpm for 30-40 seconds, and then anneal on a hot stage at 100-120°C for 10-15 minutes to obtain a hole transport layer.
6. The method for preparing a wide bandgap perovskite solar cell with high open circuit voltage according to claim 5, characterized in that: The implementation method of step 4 comprises the following steps: Step 4.1: Prepare a wide bandgap perovskite precursor solution according to the formula Cs0.1MA0.1FA0.8PbIBr1.8Cl0.2; Step 4.2: Spin the prepared wide bandgap perovskite precursor solution onto the obtained buried interface modification layer by a spin coater. The rotation speed of the spin coater is divided into two stages. The rotation speed of the first stage is 1000-2000 rpm and the spinning time is 10 s. The rotation speed of the second stage is 4000-5000 rpm and the spinning time is 40 s. At the beginning of the second stage, 0.1-0.2 mL of chlorobenzene anti-solvent is added dropwise onto the rotating substrate surface for 20-25 s. After the second stage of spin coating is completed, annealing is performed at a temperature range of 80-100°C for 10-15 min to obtain a wide bandgap perovskite light-absorbing layer.
7. The method for preparing a wide bandgap perovskite solar cell with high open circuit voltage according to claim 6, characterized in that: The method for preparing the electron transport layer in step 5 comprises the following steps: PCBM is dissolved in chlorobenzene (CB) to prepare a PCBM solution with a concentration of 15 mg / mL; the solution is spin-coated on the wide-bandgap perovskite light-absorbing layer by a spin coater at a spin coating speed of 1000 to 2000 rpm for 30 to 40 seconds, and then annealed on a hot stage at a temperature range of 100 to 120° C. for 5 to 10 minutes to obtain an electron transport layer.
8. The method for preparing a wide bandgap perovskite solar cell with high open circuit voltage according to claim 7, characterized in that: The method for preparing the buffer layer in step 5 comprises the following steps: BCP was dissolved in isopropyl alcohol (IPA) to prepare a BCP solution with a concentration of 2 mg / mL; the solution was spin-coated on the electron transport layer by a spin coater at a spin coating speed of 4000-5000 rpm for 20s-30s, and then annealed on a hot stage at a temperature range of 80-100°C for 1-3min to obtain a buffer layer.
Citation Information
Patent Citations
Preparation method of high-open-voltage wide-band-gap perovskite top cell for laminated cell
CN114373871A
Trans-perovskite solar cell, preparation method thereof and photovoltaic device
CN118019421A
Inverted perovskite solar cell with buried high-entropy 2D perovskite modification layer structure and preparation method of inverted perovskite solar cell
CN119012721A
Halide perovskite solar cell and bottom interface self-growth modification method therefor
WO2023155562A1
Precursor, perovskite light-absorbing layer and preparation method, perovskite cell, and electric device
WO2024174239A1
Cited By
Perovskite film layer, preparation method and perovskite three-junction laminated solar cell
CN121531916A
Perovskite film layer, preparation method and perovskite triple-junction stacked solar cell
CN121531916B